Diagnostic criteria of knee osteoarthritis in rheumatology outpatient clinic, Dr. Sardjito Hospital, Yogyakarta - Kertia, Nyoman; Wachid, Deddy Nur; Krishnan, P N (Indonesian Journal of Rheumatology, 2011)
Background: Osteoarthritis (OA) is a chronic condition characterized by the breakdown of joints cartilage. Approximately 25% of persons 55 years of age or older have knee pain on most days and about half of them have radiographic OA in the knee. Prevalence of knee OA increases with age and it is more common in women than men. It is not easy to establish the diagnosis of knee OA since other knee disorders have similar clinicalsigns and symptoms.Objective: The purpose of this study was to observe the diagnosis pattern of knee OA in rheumatology outpatient clinic at Dr. Sardjito Hospital based on clinical and radiographic criteria of American College of Rheumatology (ACR). Method: The design of this study was cross-sectional. Data of the patients with knee OA were investigated from their medical records. Results: There were 212 subjects diagnosed with knee OA during the year 2000â2010. Most of the subjects (90.56%) were more than 50 years old. Women were more frequent affected by OA than men. All of the subjects (100%) had knee pain. Crepitus was found in98.11% subjects. Morning stiffness less than 30 minutes was found in 86.79% subjects. Osteophyte appearances were found in 79.72% subjects.Conclusion: Knee pain, crepitus, and age more than 50 years old were the most frequent criteria used to diagnose knee OA. Morning stiffness less than 30 minutes and osteophyte appearances were also frequent in knee OA.